Kinerja Alat Pencurah Sederhana Pada Sistem Irigasi Curah (Sprinkler Irrigation System) - Saiful Rochdyanto; Sigit Supadmo Arif; Isti Susilawati (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 1997)
The modification of fabricated sprinkler which is available in the market was done in order to solve several problems, such as : the performance is unsatisfied, the prize is relatively high, the construction is complicated, and the operation and maintenance is not too easy. The performance testing was carried out to six model of modification sprinklers, they were : Sl, S2, S3, S4, S5, and S6, and then compared with fabricated sprinkler (SP). Sprinklers were tested with several parameters, such as : water discharge, throw distance, water distribution pattern, water rate, and particle water diameter. Result of experiment showed that S5 gives the best performance. This model has upper arm length = 5.0 cm, lower arm length = 3.8 cm, nozzle angle in upper arm = 65Â°, nozzle angle in lower arm = 40°, the number of nozzle in each lower arm and top of arm is one. Comparing with fabricated sprinkler (SP), the prize of S5 model is relatively cheap. It is Rp. 5,575.00 for S5 and Rp. 17,500.00 for SP. Due to the construction is relatively simple and the product material is very easy to find in local market, so the model S5 can be introduced and developed to farmers in order to increase their agricultural production.